Evaluation of efficiency index of friction energy dissipation devices using endurance time method - Amir Shirkhani; Bahman Farahmand Azar; Mohammad Charkhtab Basim (Numerical Methods in Civil Engineering)
Various methods have been presented to improve the performance of buildings against earthquakes. Friction damper device is one of the energy dissipation devices that appropriately absorbs and dissipates the input energy and decreases displacements. In this paper, the possibility of using endurance time method to determine the efficiency index and optimum slip load for these dampers was investigated by comparing the results of endurance time and nonlinear time history analyses. The efficiency indexes acquired from the average of results for nonlinear time history and endurance time analyses were close to each other. In this research, by ‎assuming identical ‎optimum slip ‎load ‎for the dampers in all ‎stories, the ‎normalized damper ‎strength was ‎increased in a number of equal ‎steps ranging from ‎zero to one to ‎determine the efficiency index of ‎dampers in each step. ‎Then, the optimum ‎slip ‎load ‎of dampers in ‎the steel frames was ‎calculated according ‎to ‎the minimum ‎efficiency index ‎of dampers.‎ As a result, employing the endurance time method instead of a high number of nonlinear time history analyses is also possible, and using the endurance time method diminishes 57% of computational endeavors.  Lastly, a relation for acquiring the optimum slip load of the friction damper devices in steel structures was proposed in terms of the weight of the structures. After adding optimal FDDs to the structures and investigating the effectiveness of the dampers, it was concluded that by using endurance time excitation function with ‎better ‎energy consistency, the endurance time results ‎could be improved.‎